Evaluation of the mechanical behavior and valorization of local materials for waste management: impermeable barriers - Fatma-Zohra Tebib; Djihene Benouaret (My University, 2024)
Containment barriers play a crucial role in waste management, particularly in engineered landfills, to prevent leaks and environmental contamination. The main characteristics sought for these barriers include low hydraulic conductivity (k ≤ 〖10〗^(-9) m/s) To minimize leaks, sufficient shear resistance To maintain the stability of the barrier with low swelling potential to avoid the creation of pores that could compromise the integrity of the barrier. This study examines six mixtures of sand and bentonite at different proportions, evaluating their performance as containment barriers through various tests: Compaction tests to determine the optimal density and compaction properties of the mixtures, Direct shear tests to assess shear strength, also swelling tests to measure swelling potential and hydraulic conductivity tests to check their ability to prevent leaks. A physical characterization of the materials was also carried out to better understand their fundamental properties. The results of this study provide recommendations for the effective use of sand/bentonite mixtures in waste containment barriers. ----------------------------------------------------------------------------------- تلعب حواجز الاحتواء دوراً حاسماً في إدارة النفايات، وخاصة في مدافن النفايات الهندسية، لمنع التسربات والتلوث البيئي. تشمل الخصائص الرئيسية المطلوبة لهذه الحواجز الموصلية الهيدروليكية المنخفضة ) k ≤〖10〗^(-9)م/ث( لتقليل التسربات، ومقاومة القص الكافية للحفاظ على استقرار الحاجز مع احتمالية تورم منخفضة لتجنب إنشاء المسام التي يمكن أن تؤثر على السلامة من الحاجز. تتناول هذه الدراسة ستة مخاليط من الرمل والبنتونيت بنسب مختلفة، وتقييم أدائها كحواجز احتواء من خلال اختبارات مختلفة: اختبارات الضغط لتحديد الكثافة المثلى وخصائص الدمك للمخاليط، اختبارات القص المباشر لتقييم قوة القص، وكذلك اختبارات التورم لقياس اختبارات احتمالية التورم والتوصيل الهيدروليكي للتحقق من قدرتها على منع التسربات. كما تم إجراء التوصيف المادي للمواد لفهم خصائصها الأساسية بشكل أفضل. تقدم نتائج هذه الدراسة توصيات للاستخدام الفعال لمخاليط الرمل / البنتونيت في حواجز احتواء النفايات. ---------------------------------------------------------------------------------- Les barrières de confinement jouent un rôle crucial dans la gestion des déchets, notamment dans les centres d'enfouissement technique, pour prévenir les fuites et la contamination environnementale. Les principales caractéristiques recherchées pour ces barrières incluent une faible conductivité hydraulique (k ≤ 〖10〗^(-9) m/s) Pour minimiser les fuites ,une résistance au cisaillement suffisante Pour maintenir la stabilité de la barrière avec un faible potentiel de gonflement pour éviter la création de pores qui pourraient compromettre l'intégrité de la barrière. Cette étude examine six mélanges de sable et de bentonite à différentes proportions, en évaluant leur performance en tant que barrières de confinement à travers divers essais :Essais de compactage pour déterminer la densité optimale et les propriétés de compactage des mélanges,Essais de cisaillement direct Pour évaluer la résistance au cisaillement aussi des essais de gonflement Pour mesurer le potentiel de gonflement et essais de conductivité hydraulique pour vérifier leur capacité à empêcher les fuites. Une caractérisation physique des matériaux a également été réalisée pour mieux comprendre leurs propriétés fondamentales. Les résultats de cette étude fournissent des recommandations pour l'utilisation efficace des mélanges sable/bentonite dans les barrières de confinement des déchets.